Amy G. Remensnyder, La Conquistadora. The Virgin Mary at War and Peace in the Old and New Worlds - Fuente, María Jesús (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
doi: https://doi.org/10.20318/revhisto.2017.3593